Toward a Radical Metaphysics of Socialism: Marx and Laruelle - Kolozova, Katerina (Brooklyn, NY punctum books, 2015)
Departing from the conventional readings of Karl Marx s Capital and other of his works, by way of François Laruelle s radicalization of concepts, Katerina Kolozova identifies a theoretical kernel in Marx s thought whose critical and interpretative force can be employed without reference to its subsequent interpretations in the philosophical mainstream. The latter entails a process of abstracting a philosophical legacy or rather, of putting it in brackets and then codifying a history of a learned interpretation established in supposed fidelity to the theoretical project of a master. Interpreting the master implies a mastery of doctrinal tools, which results in establishing a catechism of the Logos of the Master. And this catechism interferes, Kolozova argues, with more direct encounters with Marx s writings. As we know, Marx s rigorously descriptive language unravels the radical core of capitalist economic processes and, through that unraveling, also reveals capitalism s necessary exploitation and subjugation of human labor. Toward a Radical Metaphysics of Socialism attempts to recuperate and emancipate the notion of metaphysics in this scenario by virtue of radicalizing thought s encounter with the Real. Kolozova argues that this metaphysical drama is at the origin of the social and economic injustices of contemporary global economic-political realities, and she illustrates this state of affairs in discussions of the problem of wage labor, automated speculation as the core of late capitalism, the post-2008 financial crisis, the status of technology in late capitalism, sexual difference and gender, and the human and non-human body s subjugation capitalist automation
English
Keywords: Western philosophy, from c 1900 -; philosophy; speculative realism; non-philosophy; Maxism; metaphysics